Effects of a water aerobics program on the body composition of active middle-aged women - Manzano, Juan José (2011)
Objective: Describe and analyze changes in body composition of middle-aged women after participating in a water aerobics physical activity program and a subsequent detraining period. Materials and Methods: The group analyzed consisted of 17 women from Arroyo de San Serván (Badajoz), who were physically active (had participated in fitness gymnastics programs one to three sessions per week for the past three months), with an average age of 53.6 ± 9.1 years. The program was comprised of sixty minute-sessions five days a week, for 6 weeks, with a 4-week detraining period. Three anthropometric evaluations were conducted: at the beginning and at the end of the program and after the detraining period. Size and weight were recorded during each measurement, including six skinfolds, four body circumferences and three bone diameters. Fat percentage was obtained from four skinfolds (triceps, subscapular, suprailiac and abdominal) using the Yuhasz formula modified by Faulkner (1968). The muscle percentage was calculated from total mass percentage less bone percentage (Rocha, 1975), body fat percentage (Faulkner, 1968) and the residual percentage using the Wurch ́s equation (Esparza, 1993) of subjects measured, based on Matiegka ́s basic proposal (four components model). Results: after the program a significant increase was observed in muscle percentage: 32.69 ± 2.69% vs. 33.44 ± 2.89% (p <0.05), in muscle weight: 23.45 ± 3.53 kg vs. 24.02 ± 3.33 kg (p <0.05), as well as a significant decrease in the fat component reflected in the sum of skinfolds: 193.66 ± 25.54 mm vs. 188.38 ± 25.67 mm (p <0.05) and more specifically in the suprailiac skinfold, 30.47 ± 8.49 mm. vs 28.00 ± 8.78 mm (p <0.05). These trends were maintained during the detraining period, specifically in muscle percentage: 33.44 ± 2.89% vs. 34.25 ± 3.04% (p <0.01 compared to initial measurement), muscle weight: 24.02 ± 3.33 kg vs 24.74 ± 3.64 kg (p <0.01 compared to initial measurement), the sum of skinfolds: 188.38 ± 25.67 mm vs 183.41 ± 26.65 mm (p<0.05 compared to initial measurement). Conclusions: Participating in water aerobics programs for a short period of time under the conditions of this study decreases the fat component and significantly increases the muscle component in active middle-aged women.